The Effect of Tourist Relationship Perception on Destination Loyalty at a World Heritage Site in China: The Mediating Role of Overall Destination Satisfaction and Trust. (February 2017) - Su, LuJun; Hsu, Maxwell K.; Swanson, Scott
This study focuses on domestic tourists at a World Heritage Site located in China and investigates the relationship of three important visitor perceptions (i.e., service fairness, destination image, and service quality) with tourism destination loyalty (i.e., positive word-of-mouth referrals and revisit intentions) through overall destination satisfaction and trust toward destination service providers. The structural equation modeling findings generally support the conceptual model and indicate that service fairness and service quality have a significant and positive impact on overall destination satisfaction and trust toward destination service providers, while destination image has a significant effect on overall destination satisfaction but not on trust toward destination service providers. In addition, the investigated perceptions-loyalty relationships are found to be mediated by overall destination satisfaction, but not necessarily by trust toward destination service providers. The paper includes discussions of the theoretical and managerial implications of the findings.